Decoding Gimmicks of Financial Shenanigans in Telecom Sector in India - Sandeep Goel (Journal of Accounting and Management Information Systems (JAMIS), 2013)
Major corporate financial shenanigans get away in the name of creative accounting. But, they need to be studied for lessons learned and strategies to avoid or reduce the incidence of such frauds in the future. It is essential for shareholders, particularly the common man who does not have any access to the company except reported financial numbers. This paper aims to decode the level of financial shenanigans practices in corporate enterprises in telecom sector in India. The reason being is that telecom sector is a part of service industry and is dependent on tariff policies; therefore it is the most volatile sector where financial shenanigans are probable on a large scale. We have tried to contribute by detecting these shenanigans in totality not in isolation, on five parameters: quality of earnings, quality of revenue, volatility of income, discretionary accruals, and manipulation score. The results indicate the visibility of financial shenanigans in the companies under study. It is therefore expected that the study improves investors' belief of a company's performance, as reflected in their financial numbers.
Keywords: M49; 650; Financial shenanigans; quality of earnings; quality of revenue; discretionary accruals and telecom sector